Chromoblastomycosis Treatment With Combination Therapy of Itraconazole (Pulse Dose) and Cryotherapy - Nugrohoaji Dharmawan; Ahmad Fiqri (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2021)
Chromoblastomycosis is a chronic mycosis infection of the skin and subcutaneous tissue. The lesson begins with a history of trauma characterized by slowly gradual growing nodule lesions, especially in the lower extremities. Management of chromoblastomycosis may be physical and non-physical and combination to achieve the best result. A 70-year-old male farmer came with a rough lump on his left leg in the past six years ago. Lesions were multiple-verrucous, varying sizes nodules on the left limb. Skin scraps examination showed copper penny appearance or Medlar bodies. Histopathological examination showed granulomatous inflammation and Medlar bodies. In fungi culture, we obtained Fonsecaea pedrosoi. Patients were treated with a combination of Itraconazole 400 mg/day for a week for three months (pulse dose) and serial cryosurgery once per week. The combination therapy gave clinical improvement and good results. The diagnosis of chromoblastomycosis is based on history, physical examination, histopathology, and culture. Predisposing factors are working in the fields in this case and being exposed to trauma such as soil and plants. Giving combination therapy with itraconazole and cryosurgery makes good results for this patient.